Feasibility and high quality measured in the rapid expansion of telemedicine during COVID -19 for sports and musculoskeletal medicine practice - Tenforde, A. S.; Iaccarino, M. A.; Borgstrom, H.; Hefner, J. E.; Silver, J.; Ahmed, M.; Babu, A. N.; Blauwet, C. A.; Elson, L.; Eng, C.; Kotler, D.; Homer, S.; et al. (PM&R, 2020)
Introduction: The global pandemic due to SARS-CoV-2 has resulted in an expansion of telemedicine. Measures of quality and barriers for rapid use by patients and physicians are not well described. Objective: To describe results from a quality improvement initiative during rapid adoptive phase of telemedicine during the pandemic. Design: Patient and physician satisfaction with synchronous audiovisual telemedicine visits was measured during early adoptive phase (April 6-17, 2020) within the division of sports medicine in an academic Physical Medicine and Rehabilitation (PM&R) department. Patients were invited to participate in a quality improvement initiative by completing an online survey at the end of a telemedicine visit. Physicians completed a separate survey. Primary Outcome Measures: Patient measures included visit type, duration of encounter, quality, and satisfaction. Physicians reported on experiences performing telemedicine. Results: Surveys were completed by 119 patients (289 telemedicine encounters, response rate 41%) and 13 physiatrists. Telemedicine was utilized primarily for follow-up visits (n=74, 70.6%) and most common duration was 15-29 minutes. Patients rated their telemedicine visit as "excellent" or "very good" across measures (91.6-95.0%) including addressing concerns, communication, developing a treatment plan, convenience, and satisfaction. Value of completing a future telemedicine visit was measured at 84.9%. Most reported estimated travel time saved in excess of 30 minutes. Rate of no-show was 2.8%. Most physicians (62%) had no prior experience with telemedicine visits, and most were comfortable performing these visits after completing 1-4 sessions (69%). Nearly all physicians (92%) rated their telemedicine experience as very good or excellent. The key barrier identified for telemedicine was technical issues. All physicians reported plans to perform telemedicine visits if reimbursement continues. Conclusions: In summary, rapid expansion of telemedicine during COVID-19 pandemic was well-received by a majority of patients and physicians. This suggests feasibility in rapid expansion of telemedicine for other outpatient sports medicine practices.